Muhasabah An-Nafs untuk Mengenali Potensi Diri Siswa di Madrasah Aliyah Swasta Miftahussalam Medan - Reza Imelda; Muhammad Yunan Harahap (STKIP PGRI SITUBONDO, 2023)
Abstract: In order for the potential of students to develop, an effective learning method is needed. Therefore, this research describes how the implementation of Muhasabah An-Nafs in the learning process and whether this method can help students of Madrasah Aliyah Miftahussalam Medan to recognize and discover their potential. In this study, researchers used a type of descriptive qualitative approach which contains complex descriptions and views of respondents. Collection of data sources taken by researchers based on observational data, interviews, and documentation, then concluded through an analysis model with stages; data reduction, data presentation and conclusion. The first result obtained from this study is that Muhasabah An-Nafs has a good impact on students and for the school, so that teachers and students have good self-control and can recognize themselves so that they become quality graduates. The results of the two studies with Muhasabah An-Nafs can also help students recognize their own potential by opening their horizons of thinking to be wider so that they reap achievements from the potential they have.